Measuring the Impact of the Approach to Migration in the Quality of Web Service Interfaces - Mateos Diaz, Cristian Maximiliano (2015)
There is a good consensus on the strategic value of service-oriented architecture (SOA) as a way of structuring systems, and a common trend is to migrate legacy applications that use outdated technologies and architectures to SOA. We study the effects in the resulting Web Service interfaces of applying two traditional migration approaches combined with common ways of building services, namely, direct migration with code-first and indirect migration with contract-first. The migrated system was a 35-year-old COBOL system of a government agency that serves several millions of users. In addition, we provide a deep explanation of the trade-offs involved in following either combinations. Results confirm that the ‘fast and cheap’ approach to move into SOA, which is commonplace in the industry, may deliver poor service interfaces, and interface quality is also subject to the tools supporting the migration process.